Voice in the Wilderness Conversations with Terry Tempest Williams - Austin, Michael (University Press of Colorado, 2006)
With her distinctive, impassioned voice and familiar felicity of language, Terry Tempest Williams talks about wilderness and wildlife, place and eroticism, art and literature, democracy and politics, family and heritage, Mormonism and religion, writing and creativity, and other subjects that engage her agile mind-in a set of interviews gathered and introduced by Michael Austin to represent the span of her career as a naturalist, author, and activist.